2022
DOI: 10.47162/rjme.62.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and adipose tissue inflammation in NASH: correlations with histopathological aspects

Abstract: Introduction: Non-alcoholic steatohepatitis (NASH) is a progressive form of liver steatosis that involves a risk of progression towards fibrosis, cirrhosis, and end-stage liver disease. Low-grade inflammation is recognized to be involved in non-alcoholic fatty liver disease (NAFLD) pathogeny. Additionally, adipose tissue dysfunction plays an important role in the development of metabolic diseases. Patients, Materials and Methods:We conducted a study on 68 patients with liver steatosis confirmed through liver b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Leptin concentrations in the peripheral blood of obese people is proportional to the degree of obesity [ 32 ], and hyper-leptinemia promotes steatosis with or without NAFLD [ 33 , 34 ]. Indeed, the adipose tissue disfunction in NAFLD is not completely understood but the inflammation of specific depots of white adipose tissue has a key role in NAFLD progression [ 35 , 36 ]. Thus, it is conceivable that in the cluster of NAFLD/NASH group with higher leptin levels, which strongly indicated that a higher BMI, the adipose tissues may be more responsible for circulating leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin concentrations in the peripheral blood of obese people is proportional to the degree of obesity [ 32 ], and hyper-leptinemia promotes steatosis with or without NAFLD [ 33 , 34 ]. Indeed, the adipose tissue disfunction in NAFLD is not completely understood but the inflammation of specific depots of white adipose tissue has a key role in NAFLD progression [ 35 , 36 ]. Thus, it is conceivable that in the cluster of NAFLD/NASH group with higher leptin levels, which strongly indicated that a higher BMI, the adipose tissues may be more responsible for circulating leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the cluster of differentiation T-lymphocytes, CD8 + T cells were recently found to infiltrate in the liver of MAFLD patients together with a higher degree of steatosis, similar to the Th cells that were derived from CD4 + T cells [114]. Another clinical study showed the higher frequencies of IL-7Rα low CD8 + T cells and IL-7Rα low CX3CR1 + CD8 + T cells but not CD4 + T cells in the serum of obese children, compared to the children without metabolic syndrome [115].…”
Section: Effects Of Cd8 + T Cells On Mafldmentioning
confidence: 95%
“…64 Within the liver, resident macrophages (KCs) shift to an M1 proinflammatory macrophage phenotype during the transition from simple steatosis to NASH, increasing proinflammatory cytokine production and systemic inflammation correlating with the severity of steatosis and NASH. 65,66 Activated KCs in NASH become dysfunctional over time, leading to reduced filtration of bacterial components absorbed into the portal tract from the gut, 67 elevating serum proinflammatory cytokines that could reach the CNS. In fact, TNF-α correlates with severity of fibrosis in NASH patients and readily crosses the BBB.…”
Section: Nafld Drives Systemic Inflammation Potentially Contributing ...mentioning
confidence: 99%